Guinea-Bissau : Poverty Reduction Strategy Paper-Second Annual Progress Report. (IMF Staff Country Reports; Country Report, 2010)
Guinea-Bissau's first National Poverty Reduction Strategy Paper (NPRSP) established the strategic directions, primary objectives, and commitments by the country and its people to reduce poverty and achieve the MDGs. The main objectives of the second NPRS are to make progress toward achievement of the MDGs, to improve macroeconomic management, and consolidate administrative reforms to ensure the quality provision of basic public services. It is expected that the second NPRSP will perform well in implementing priorities than the first NPRSP and will help Guinea-Bissau to attain the completion point under both the HIPC and MDRI programs.